Interest Spreads in Banking : Costs, Financial Taxation, Market Power, and Loan Quality in the Colombian Case 1974-96 - Barajas, Adolfo (IMF Working Papers; Working Paper ;, 1998)
This paper examines the determinants of the high intermediation spread observed in the Colombian banking sector for over two decades. A reduced-form equation is estimated on the basis of a bank profit maximization model that permits a decomposition into operational costs, financial taxation, market power, and loan quality. Although the average spread did not change between the pre liberalization (1974-88) and post liberalization (1991-96) periods, its composition did, with market power being significantly reduced and the responsiveness to loan quality increased. Colombia's progress in reducing operational costs and financial taxation and improving loan quality, will determine whether it can narrow the spread.